2021
DOI: 10.3167/latiss.2021.140304
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of online teaching and learning tools

Abstract: This study investigates how students in a distance-learning upperlevel accounting course perceive the effectiveness of different online teaching and learning (OTL) tools that are commonly used in business courses taught online. This topic is of critical importance, especially as the COVID-19 pandemic has pushed more courses to be OTL. A midsemester anonymous survey in an Accounting course at a public US university was conducted to measure students’ perceptions about different OTL course tools. Students were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Asynchronous discussion forums as an e-tool provide students with the opportunity to interactively discuss, share and reflect on their own understanding based on others' perspectives and experiences at a time that is convenient for them, and, in so doing, enhancing their learning experience (Ferrara et al, 1991;Kelly et al, 2022;Makinster et al, 2006;Seethamraju, 2014;Stacey, 1999;Weila et al, 2011). Discussion forums facilitate interaction and engagement with the content and with peers, enabling independent learning, developing critical thinking skills; leading to the social construction of knowledge; and the transferring of knowledge beyond the traditional lecture environment (Abdel-Rahim, 2021;Seethamraju, 2014;Weila et al, 2011). Wang and Bonk's (2001) study indicated the possibility that the permanence of recorded information on a discussion forum could make students reluctant to use the platform or that some might be afraid of asking a question that may be regarded as stupid.…”
Section: Discussion Forummentioning
confidence: 99%
See 1 more Smart Citation
“…Asynchronous discussion forums as an e-tool provide students with the opportunity to interactively discuss, share and reflect on their own understanding based on others' perspectives and experiences at a time that is convenient for them, and, in so doing, enhancing their learning experience (Ferrara et al, 1991;Kelly et al, 2022;Makinster et al, 2006;Seethamraju, 2014;Stacey, 1999;Weila et al, 2011). Discussion forums facilitate interaction and engagement with the content and with peers, enabling independent learning, developing critical thinking skills; leading to the social construction of knowledge; and the transferring of knowledge beyond the traditional lecture environment (Abdel-Rahim, 2021;Seethamraju, 2014;Weila et al, 2011). Wang and Bonk's (2001) study indicated the possibility that the permanence of recorded information on a discussion forum could make students reluctant to use the platform or that some might be afraid of asking a question that may be regarded as stupid.…”
Section: Discussion Forummentioning
confidence: 99%
“…To decide on the best course of action, it is crucial to reflect on the experiences gained during the COVID-19 pandemic (Du Plessis et al, 2022) which can inform teaching and learning approaches (Abdel-Rahim, 2021;Fogarty, 2020;Marton and S€ alj€ o, 1997;McGuigan, 2021). As an area for future research, Sangster et al (2020, p. 444) recommended exploring accounting students' experiences as such research "would enrich the field of accounting education research" and will inform practices for the future.…”
Section: Introductionmentioning
confidence: 99%
“…Effective instructional strategies included direct interaction with instructors and small group collaborations. Results of a study conducted by Abdel-Rahim ( 2021 ) showed that the most useful non-interactive instructional activities were practice exercises and quizzes.…”
Section: Online Course Activities and Strategiesmentioning
confidence: 99%
“…Students seem to value interactions with their instructors more than interactions with their peers. When considering interactive activities, virtual office hours and email exchanges with instructors were more helpful than discussion boards or group work (Abdel-Rahim, 2021 ). Martin and Bolliger ( 2018 ) who investigated students’ perceptions pertaining to the importance of online engagement strategies found that students valued learner-to-instructor strategies more than learner-to-learner and learner-to-content.…”
Section: Online Course Activities and Strategiesmentioning
confidence: 99%
“…By embracing online teaching methods, educational institutions can enhance their preparedness for potential disruptions and ensure continued educational delivery in challenging circumstances. The importance of flexible and adaptable teaching approaches, making the incorporation of OTL strategies a significant consideration for education, was highlighted [20] [21].…”
Section: Literature Reviewmentioning
confidence: 99%